Life table and demographic parameters of the coccinellid predatory species, Hippodamia convergens Guérin-Méneville (Coleoptera: Coccinellidae) when fed on two aphid species - Muhammad Arshad; Muhammad Irfan Ullah; Umair Shahid; Muhammad Tahir; Malik Imran Khan; Muhammad Rizwan; Muhammad Abrar; Muhammad Mubashar Niaz (Egyptian Journal of Biological Pest Control, 2020)
Abstract The study aimed to determine the effect of two aphid species; Lipaphis erysimi (Kaltenbach) and Aphis gossypii Glover (Hemiptera: Aphididae) on life table and demographic parameters of Hippodamia convergens Gu`erin-M´eneville (Coleoptera: Coccinellidae). The developmental period of all life stages of H. convergens was shorter when fed on L. erysimi. Net reproductive rate (R o) was higher (159.85 offspring/individual) on L. erysimi, while it was 87.85 offspring/individual on A. gossypii. Mean generation time (T) was shorter (30.49 d) on L. erysimi than on A. gossypii (45.1 days). Values of the intrinsic rate of increase (r) and finite rate of increase (λ) were calculated as 0.166 days−1 and 1.181 days−1, respectively, on L. erysimi that were higher than on A. gossypii (0.099 days−1 and 1.104 days−1, respectively). Similarly, the survival rate was also higher when the predator was fed on L. erysimi. Overall, the findings suggest using L. erysimi as a better source of prey than A. gossypii for rearing H. convergens.